2016
DOI: 10.18632/oncotarget.14220
|View full text |Cite
|
Sign up to set email alerts
|

Sensitizing leukemia stem cells to NF-κB inhibitor treatment in vivo by inactivation of both TNF and IL-1 signaling

Abstract: We previously reported that autocrine TNF-α (TNF) is responsible for JNK pathway activation in a subset of acute myeloid leukemia (AML) patient samples, providing a survival/proliferation signaling parallel to NF-κB in AML stem cells (LSCs). In this study, we report that most TNF-expressing AML cells (LCs) also express another pro-inflammatory cytokine, IL1β, which acts in a parallel manner. TNF was produced primarily by LSCs and leukemic progenitors (LPs), whereas IL1β was mainly produced by partially differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 55 publications
(55 reference statements)
1
21
0
Order By: Relevance
“…As a result, IRAK1/4 inhibitor treatment caused increased survival and impaired LSC function in the MLL-AF9 mouse model of AML ( 97 ). This novel mechanism could account for some of the activity of IL-1 pathway inhibitors reported in other studies in secondary AML, and specifically in MLL-AF9 AML ( 98 ). Together, these results suggest that there may be differences in how leukemic blasts and LSCs regulate IL-1β expression and respond to IL-1β, and that there may be differential dose-dependent effects of IL-1β on both normal HSPCs and LSCs.…”
Section: Il-1βmentioning
confidence: 60%
“…As a result, IRAK1/4 inhibitor treatment caused increased survival and impaired LSC function in the MLL-AF9 mouse model of AML ( 97 ). This novel mechanism could account for some of the activity of IL-1 pathway inhibitors reported in other studies in secondary AML, and specifically in MLL-AF9 AML ( 98 ). Together, these results suggest that there may be differences in how leukemic blasts and LSCs regulate IL-1β expression and respond to IL-1β, and that there may be differential dose-dependent effects of IL-1β on both normal HSPCs and LSCs.…”
Section: Il-1βmentioning
confidence: 60%
“…After the NF-κB pathway was activated, the gene transcription of an array of pro-inflammatory mediators and inflammatory cytokines, including IL-1b and TNF-α, is induced. 29 It has been reported that NF-κB pathway downregulates the expression of AQP5 in AR rats, by inhibiting p-CREB. Wang et al 19 showed that this signal cascade works through increased transcription of IL-1b while Skowron-zwarg et al 30 demonstrated that TNF-α was involved and suppressed cAMP-response element-dependent gene expression by competitive binding to CREB-binding protein.…”
Section: Discussionmentioning
confidence: 99%
“…The first approach could ameliorate the clinical progress in CIA more than the single treatments did [395]. Additionally, RA patients were treated with the combination of IL1 and TNF neutralizing drugs although this therapy did not have added value [396], although this strategy seemed promising in preclinical sepsis models and in acute myeloid leukemia [76,397]. However, the complete blockage of host defense mechanisms should be kept in mind as a plausible destructive side effect.…”
Section: Multispecific Approachesmentioning
confidence: 99%